Perilaku Sticky Cost Biaya Penjualan, Biaya Administrasi dan Umum Serta Harga Pokok Penjualan Pada Perusahaan Manufaktur - Lea Ratnawati; Yeterina Widi Nugrahanti (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
The objective of this study is to find the indication of sticky cost behavior in Indonesian manufacturing. The cost stickiness can be indicated by asymetric reaction of costs to changes. This study employs Anderson, Banker, Janakiraman (ABJ) model to identify the sticky cost behaviour on selling expense and general administrative expense. The samples of this study are 351 firm years of manufacturing companies listed in Indonesia Stock Exchange during 2009-2012. This study found that selling, general and administrative cost increase 0,475 percent and cost of good sold increase 1,063 percent when sales increase 1 percent. Whereas, the sales and selling, general and administrative cost decrease 0,409 percent and cost of good sold decrease 0,033 percent per1 percent decrease in sales. The research results provide of sticky cost behaviour indication in selling expense, general and administrative, and cost of good sold in Indonesian manufacturing company. The findings support the theory of cost adjustment delay.